Preoperative left ventricular hypertrophy is associated with reduced patient survival after liver transplantation. (26th December 2013) - Darstein, F.; König, C.; Hoppe‐Lotichius, M.; Grimm, D.; Knapstein, J.; Mittler, J.; Zimmermann, A.; Otto, G.; Lang, H.; Galle, P.R.; Zimmermann, T.
Abstract Left ventricular hypertrophy (LVH) has been described in the context of cirrhotic cardiomyopathy. The influence of LVH on survival of liver transplant (LT) recipients has not been clarified. Therefore, we evaluated the effect of LVH on survival in LT recipients. In total, data from 352 LT patients were analyzed. LVH was diagnosed by echocardiographic measurement of left ventricular wall thickness before LT. Patients were followed up for a mean of 4.2 yr. LVH was diagnosed in 135 (38.4%) patients. Patients with LVH had significantly more frequently male gender (p = 0.046), diastolic dysfunction (p < 0.001), and hepatocellular carcinoma (HCC; p = 0.004). Furthermore, LVH patients were older (p < 0.001) and had a higher body mass index (BMI; p = 0.001). There was no difference in frequency of arterial hypertension, pre‐transplant diabetes mellitus, or etiology of liver cirrhosis. Patients without LVH had a better survival (log rank: p = 0.05) compared with LVH patients. In a multivariate Cox regression LVH (p = 0.031), end‐stage renal disease (ESRD; p = 0.003) and lack of arterial hypertension (p = 0.004) but not MELD score (p = 0.885) were associated with poorer survival. Conclusion LVH is frequently diagnosed in patients on the waiting list and influences survival after LT.